Imaging characteristics of temporopolar blurring in the context of hippocampal sclerosis. Issue 1 (15th February 2022) - Clavijo Prado, Carlos Andrés; Federico, Paolo; Bernasconi, Andrea; Bernhardt, Boris; Caciagli, Lorenzo; Concha, Luis; Chinvarun, Yotin; Jackson, Graeme; Morgan, Victoria; Rampp, Stefan; Vaudano, Anna Elisabetta; Wang, Irene; et al.
Abstract: We present an illustrative case to address anterior temporal lobe atrophy with poor delineation of the temporopolar gray‐white matter interface based on T2‐weighted and fluid‐attenuated inversion recovery (FLAIR) images in patients with temporal lobe epilepsy associated with hippocampal sclerosis (TLE‐HS). A 52‐year‐old woman with pharmacoresistant seizures since the age of six months underwent a previous MRI scan using a suboptimal protocol which was reported as unremarkable. MRI performed according to an epilepsy protocol showed classic signs of left HS and ipsilateral temporal polar atrophy with blurring of the gray‐white matter boundary on FLAIR images. She underwent a left amygdalohippocampectomy and anterior temporal resection and remains seizure‐free after 24 months. Histopathological analyses showed HS and no signs of focal cortical dysplasia (FCD). Blurring and atrophy of the ipsilateral temporal pole are common in TLE‐HS and often misinterpreted as FCD. This relates to delayed myelination in patients with seizures before the age of two, is more pronounced on FLAIR sequences, and gives a false impression of cortical thickening. However, the T1‐weighted images show a relatively well‐demarcated cortical‐subcortical transition and normal cortical thickness. By contrast, the cortical thickening in FCD is observed on both T1‐weighted and FLAIR images. Since FCD also occurs in temporal lobe regions, it is important to differentiate the extra‐hippocampal MRI abnormalities in TLE‐HS from those likely to be FCD. This case highlights the importance of evaluation based on detailed imaging, which should always be conducted considering the EEG, seizure semiology, and other clinical information.